Degenerative Suspensory Ligament Desmitis (DSLD) in Peruvian Paso Horses Is Characterized by Altered Expression of TGFβ Signaling Components in Adipose-Derived Stromal Fibroblasts - Luo, Wei; Sandy, John; Trella, Katie; Gorski, Daniel; Gao, Shuguang; Li, Jun; Brounts, Sabrina; Galante, Jorge; Plaas, Anna (PLOS ONE, 2016)
Equine degenerative suspensory ligament desmitis (DSLD) in Peruvian Paso horses typically presents at 7–15 years and is characterized by lameness, focal disorganization of collagen fibrils, and chondroid deposition in the body of the ligament. With the aim of developing a test for disease risk (that can be used to screen horses before breeding) we have quantified the expression of 76 TGFβ-signaling target genes in adipose-derived stromal fibroblasts (ADSCs) from six DSLD-affected and five unaffected Paso horses. Remarkably, 35 of the genes showed lower expression (p<0.05) in cells from DSLD-affected animals and this differential was largely eliminated by addition of exogenous TGFβ1. Moreover, TGFβ1-mediated effects on expression were prevented by the TGFβR1/2 inhibitor LY2109761, showing that the signaling was via a TGFβR1/2 complex. The genes affected by the pathology indicate that it is associated with a generalized metabolic disturbance, since some of those most markedly altered in DSLD cells (ATF3, MAPK14, ACVRL1 (ALK1), SMAD6, FOS, CREBBP, NFKBIA, and TGFBR2) represent master-regulators in a wide range of cellular metabolic responses.